PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMPK STA. THERESIA LAMAHORA - Lyany, Elisabeth Gunu; Dominikus, Wara Sabon; Udil, Patrisius Afrisno (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
This study aimed to improve student learning outcomes in social arithmetic material by applying an ethnomathematics-based Realistic Mathematics Learning (PMR) approach to class VII students of SMPK Sta. Theresia Lamahora, Lembata Regency. The type of research used in this research is Classroom Action Research which is carried out in four meetings divided into two cycles, with every cycle consisting of two meetings. Data collection techniques in this study were through observation, learning achievement tests, and student response questionnaires, while data analysis techniques and results were descriptive, qualitative, and quantitative. The results of the study showed an increase in student learning outcomes as follows: 1) student learning outcomes that experienced an increase were indicated by the percentage of completeness of the class, which increased from 66,6% to 93,3%; 2) results of observations of teacher activity observations increased from 95,6% to 97,2%; 3) and results of observations of student activity observations increased from 92,1% to 97,6%. Thus, it can be concluded that student learning outcomes increased after implementing realistic mathematics learning based on the Du Hope Gelu Gafe activity in class VII SMPK Sta. Theresia Lamahora, Lembata Regency